2016
DOI: 10.1002/apj.1982
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of the effect of ionic surfactant/polymer on oil–water interface using dissipative particle dynamics

Abstract: Effects of the ionic surfactant (cetyltrimethylammonium bromide) and polymer (styrene-maleic acid copolymers) on the oil/water interface are studied using dissipative particle dynamics at the mesoscopic scale. Effects of the water content on equilibrated morphology of the oil/water emulsion are studied with the help of ionic surfactant. In addition, oil/water emulsion has the patterns of the compound emulsifier at the very low and very high water content. The interfacial tension increases, reaches maximum, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Unlike SCFT, DPD can describe the IFT variation and aggregation of surfactants into spherical micelles near the CMC. Wang et al investigated the behaviors of water/surfactant/oil systems through multiple DPD simulations considering different ionic/nonionic surfactant molecules and different combinations of these molecules. Effects of cationic (cetyltrimethylammonium bromide, CTAB), anionic (sodium dodecyl benzene sulfonate, SDBS), and nonionic (polyethylene oxide and polypropylene oxide in a linear form, PEO-PPO-PEO) surfactant molecules were considered at various temperatures, surfactant concentrations, and water/oil ratios. They found that increasing temperature causes the IFT to decrease and the radius of gyration to increase in all cases.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike SCFT, DPD can describe the IFT variation and aggregation of surfactants into spherical micelles near the CMC. Wang et al investigated the behaviors of water/surfactant/oil systems through multiple DPD simulations considering different ionic/nonionic surfactant molecules and different combinations of these molecules. Effects of cationic (cetyltrimethylammonium bromide, CTAB), anionic (sodium dodecyl benzene sulfonate, SDBS), and nonionic (polyethylene oxide and polypropylene oxide in a linear form, PEO-PPO-PEO) surfactant molecules were considered at various temperatures, surfactant concentrations, and water/oil ratios. They found that increasing temperature causes the IFT to decrease and the radius of gyration to increase in all cases.…”
Section: Introductionmentioning
confidence: 99%
“…A pendant drop interfacial rheometer was chosen because it harmonically increases and decreases the interfacial area. The following equation describes the harmonic expansion/compression of the liquid interfacial area A with the angular frequency ω and the oscillation of the IFT γ , because of the adsorption layer at the interface being expanded and compressed:…”
Section: Methodsmentioning
confidence: 99%
“…If the interface layer is viscoelastic, it can be described in the complex form E=E+italiciEnormal′′ where E′ is the storage modulus and E ′′ is the loss modulus …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations